Anti-Tubercular Activity Of Fluoro Benzothiazole Comprising Potent Thaizolidinone - B.S. SATHE; E. JAYCHANDRAN; V. A. JAGTAP; G.M SREENIVASA (International Journal of Pharma and Bio Sciences, 2010)
4-Fluoro-3-chloroanilline treated with Potassium thiocyanate in presence of Glacial acetic acid and bromine was converted into 2-amino-6-fluoro-7-chlorobenzothiazole. The synthesized compound in presence of m-nitro benzaldehyde refluxed in ethanol to obtained 3-[6'-fluoro-7'-chloro(1',3') benzo thiazol-2'-yl]-m-nitrophenyl(1,3) thiazolidine-4-one. The above said compound was treated with ortho, meta and para nitroanillines, ortho, meta, para chloroanillines, morpholino, Piperazine, diphenylamine in the presence of DMF to obtain different derivatives. Some compounds showed promising antimycobacterial activity.